On the TGF/Lightning Ratio Asymmetry. Issue 12 (21st June 2019) - Fabró, Ferran; Montanyà, Joan; van der Velde, Oscar A.; Pineda, Nicolau; Williams, Earle R.
Abstract: Africa is one of the most productive lightning regions on Earth, yet it has a lower terrestrial gamma ray flash (TGF)‐to‐lightning ratio especially compared with Central America. In this paper, we have analyzed the global distribution of different meteorological parameters in order to explain the TGF/lightning ratio asymmetry. We show here that a drier surface and larger Convective Available Potential Energy in Africa may produce thunderstorms with intense electric charge regions but elevated in the atmosphere and closer to each other, which allows for higher flash rates and less energetic, shorter, and smaller flashes. The results we present here suggest that continental thunderstorms in Africa more rarely fulfill the lightning and thundercloud requirements for TGF production inferred from observations and models. Key Points: Drier surface and high CAPE in Africa allows for stronger updrafts, and large concentrations of aerosols enhance electrification processes Thunderstorms in Africa may have intense electrification, but charge regions are elevated in the atmosphere and closer to each other Thunderstorms in Africa do not accomplish the favorable conditions for TGF production